2001
DOI: 10.2466/pr0.2001.89.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Associations of Temperament with Love-Styles

Abstract: University students (439 women, 111 men) completed a questionnaire that included items assessing temperament and love-styles. While a single temperament and love-style association characterized the men, all five temperament dimensions were predictive of certain of the love-styles for the women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In addition to these major findings, this study also produced some other interesting results. Consistent with the literature on romantic attitudes (Neto, ; Rotenberg & Korol, ; Sprecher & Toro‐Morn, ; Worobey, 2001a, 2001b) as well as many of the findings of Yeh and colleagues () regarding filial piety, female young adults endorsed the Agape love attitude more weakly but RFP more strongly than did males. These findings are in accordance with the gender roles described in the literature.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to these major findings, this study also produced some other interesting results. Consistent with the literature on romantic attitudes (Neto, ; Rotenberg & Korol, ; Sprecher & Toro‐Morn, ; Worobey, 2001a, 2001b) as well as many of the findings of Yeh and colleagues () regarding filial piety, female young adults endorsed the Agape love attitude more weakly but RFP more strongly than did males. These findings are in accordance with the gender roles described in the literature.…”
Section: Discussionsupporting
confidence: 83%
“…There has been much empirical research on attitudes about romantic relationships. Some studies investigated whether attitudes about love vary depending on age, gender, or romantic behaviors (Dion & Dion, ; Shulman & Scharf, ; Worobey, ). Other studies focused on love attitudes' associations with temperament and personality (Arnold & Thompson, ; Fehr & Broughton, ; Worobey, ).…”
Section: Chinese Young Adults' Attitudes Toward Their Parents: Filialmentioning
confidence: 99%
“…A number of studies reported that women favored the style of Agape more than men (e.g., Davies, 2001;Schultz et al, 2001). In contrast, other research indicated men scored higher on Agape (e.g., Fallon & Bowles, 1999;Grote & Frieze, 1998;Heaven, Da Silva, Carey, & Holen, 2004;Kunkel & Burleson, 2003;Sprecher & Toro-Morn, 2002;Worobey, 2001). The inconsistencies in these results may be due to the fact that most love-style studies were conducted to contrast and compare different love styles and did not focus on one style of love.…”
Section: Marriage and Family Reviewmentioning
confidence: 66%
“…It could be more justified to conceive love styles in more trait-like fashion, which are in turn based on some more general personality traits (cf. Worobey, 2001;White et al, 2004). For example, according to Zuckerman, Tushup and Firmer (1976), high sensation seekers are freer in their sexual behavior, so it would not be surprising if they would be found to be inclined toward the Ludic love style.…”
Section: Discussionmentioning
confidence: 99%